Enhancing Digital Literacy through Chat GPT: The Impact on Islamic Education Research Skills Among Students at State Islamic University - Fia Ayu Putri Agustin; Ovi Wulandari; Evi Fatimatur Rusydiyah (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2024)
The application of Chat GPT, an artificial intelligence model, to deepen understanding and improve digital literacy is one of the important technological advances. The purpose of the study was to determine the effect of Chat GPT in enhancing the digital literacy skills of Islamic Education students at UINSA and the urgency of using Chat GPT in Islamic education research. This research includes quantitative research. The data collection technique used a questionnaire with a choice of 4 answers, namely: 1) Strongly Agree (SS) = score 5, 2) Agree (S) = score 4, 3) Agree enough (CS) = score 3, 4) Disagree (TS) = score 2, and 5) Agree (S) = score 1. The data analysis technique uses two types of tests, namely the linearity test to determine whether there is a relationship between the independent variable and the dependent variable and the simple regression test to determine whether there is an influence of the independent variable on the dependent variable. The sampling technique used nonprobability sampling with a purposive sample type with Islamic education research variables at UIN Sunan Ampel Surabaya. Informants who were sampled amounted to 20 students. Research using Paul Gilster's digital literacy theory approach resulted in the following conclusions: (1) the results of the linearity test with a value (sig) of 0.183> 0.05 means that there is a relationship between Chat GPT and the digital literacy of Postgraduate PAI students. (2) The results of the simple regression test with a value (sig) of 0.000 <0.05 means that Chat GPT has a significant influence on the digital literacy of Postgraduate PAI students. This study's results indicate that Chat GBT's use contributes to improving students' digital literacy skills, especially in the quality of online research.